Combined Risks of Hyperlipidemia and Hypertension for Coronary Heart Disease: A Case-Control Study of the Local Population of Bahawalpur, Pakistan - kausar, Tasleem; Aslam, Madiha; Talib, Saima; Tariq, Nabeela (Current Trends in OMICS, 2022)
Hypercholesterolemia, being one of the most important risk factors for coronary heart disease, is defined as a total cholesterol concentration of ≥240 mg/dL. Hypertension has become a major public health hazard all over the world due to the serious damage it causes to the body organs and the many complications it induces, including the coronary heart disease. The current study aimed to evaluate the combined risks of correlation between hypertension and hyperlipidemia and their association with coronary heart disease. It included 100 patients diagnosed with hypertension and hyperlipidemia, as well as 100 healthy individuals of the same age and background. A standardized questionnaire was used to collect the family history of patients and control. Blood samples with a volume of 3-5ml were drawn from all patients to analyze the composition of blood serum including LDL (low-density lipoprotein), HDL (high-density lipoprotein), triglyceride, and cholesterol levels. The frequencies of all concerned factors were calculated and the mean values of blood pressure, cholesterol, LDL, and HDL were found to be in the hazardous range in patients. The data were analyzed using the chi-square test and binomial regression statistical analysis. The analysis of risk factors revealed that age, BMI (body mass index), high blood pressure, smoking, and high salt intake had a significant association with the high lipid profile in the patients. The risk of cardiovascular diseases (CVDs) is enhanced in patients with high blood pressure and hyperlipidemia.